Data, privacy laws and firm production: Evidence from the GDPR - Mert Demirer; Diego Jiménez Hernández; Dean Li; Sida Peng (Federal Reserve Bank of Chicago, 2024)
By regulating how firms collect, store, and use data, privacy laws may change the role of data in production and alter firm demand for information technology inputs. We study how firms respond to privacy laws in the context of the EU's General Data Protection Regulation (GDPR) by using seven years of data from a large global cloudcomputing provider. Our difference-in-difference estimates indicate that, in response to the GDPR, EU firms decreased data storage by 26% and data processing by 15% relative to comparable US firms, becoming less "data-intensive." To estimate the costs of the GDPR for firms, we propose and estimate a production function where data and computation serve as inputs to the production of "information." We find that data and computation are strong complements in production and that firm responses are consistent with the GDPR representing a 20% increase in the cost of data on average. Variation in the firm-level effects of the GDPR and industry-level exposure to data, however, drives significant heterogeneity in our estimates of the impact of the GDPR on production costs.
Keywords: L51; L86; D22; L11; 330; privacy laws; production function; GDPR; data; cloud computing